Investigating English Pronunciation 2015
DOI: 10.1057/9781137509437_4
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Accents: Scottish Children with English Parents

Abstract: We discuss accent mixture and the creation of idiosyncratic phonological systems in acquisition, with a focus on Scottish English. Such mixing is in addition to the relatively stable sociolinguistic systems of variation expected within a speech community, and arises when parents have radically different accents from each other or from the child's peers or other adult models. In terms of traditional geographic dialectology, there are a number of isoglosses around the Scotland/England border, but modern social m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Parents are the primary sources of input in the formative years, and thus in this study we see strong correspondences between properties of the input and properties of the children's output. In mixed-dialects environments, children may adopt accent features of both fathers and mothers (e.g., Thomas & Scobbie, 2015). However, this input-production relation is often overridden by peer effects or community norms as children get older.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parents are the primary sources of input in the formative years, and thus in this study we see strong correspondences between properties of the input and properties of the children's output. In mixed-dialects environments, children may adopt accent features of both fathers and mothers (e.g., Thomas & Scobbie, 2015). However, this input-production relation is often overridden by peer effects or community norms as children get older.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examined this input-production relationship have shown that speech properties of child production reflect specific properties of the caregiver input, especially in the early developmental years. Thomas and Scobbie (2015), for example, examined the FACE and GOAT vowels of a Glasgow boy aged 3;1 raised by parents with different British English accents; his father spoke Scottish Standard English (SSE), while his mother's accent closely resembled Southern Standard British English (SSBE). For the FACE lexical set, the boy used the SSBE [eɪ] predominantly, reflecting the accent of his mother.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, pronunciation assessment tends to focus on standard varieties of English. This is because varieties tend to lack the sort of accepted codification typically required by applied linguists as a foundation, whether in building resources in language learning, language teaching, or speech technology, or in a particular area of interest, such as clinical and development assessments of typical phonological acquisition (Thomas & Scobbie, 2015). In the context of speech technology, Praat is the proper device to be applied (Boersma et al, 2007).…”
Section: Introductionmentioning
confidence: 99%